Ultra-high performance concrete and preparation method thereof

By using modified nano silica sol and wetting agent in ultra-high performance concrete, the problems of low tensile strength, high brittleness and poor volume stability of existing ultra-high performance concrete are solved, and high compressive strength is achieved , good durability and construction performance.

CN119390420APending Publication Date: 2025-02-07SHANDONG SHENGSHIDA TECH CO LTD

Patent Information

Application Number
CN202411429619.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing ultra-high performance concrete has defects in the low tensile strength, high brittleness, poor volume stability, etc. At the same time, the investment in steel structures is large, the fire resistance performance is poor, and the easy corrosion is easy.

Method used

Modified nanosilica sol and wetting agent, and the modified nanosilica sol grafted a silane coupling agent with carboxyl groups on the surface of nanoparticles, increasing the electrostatic repulsion and steric hindrance between particles, and Add wetting agents to reduce surface tension and improve fiber encapsulation.

Benefits of technology

The internal structure of ultra-high performance concrete is achieved, and the compressive strength is stable at more than 200MPa under normal temperature maintenance, which improves durability and impact resistance, has good construction properties, and significantly enhanced mechanical properties and durability properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390420A_ABST
    Figure CN119390420A_ABST
Patent Text Reader

Abstract

The invention provides ultra-high performance concrete and a preparation method thereof, and belongs to the technical field of building materials. The concrete is prepared from cement, silica fume, mineral powder, fly ash, coarse sand, fine sand, a high-performance water reducing agent, a defoaming agent, a retarder, water, steel fibers, modified nano-silica sol and a wetting agent. Wherein the modified nano silicon dioxide sol is prepared by the following method: reacting a double-bond-containing silane coupling agent with unsaturated olefine acid to obtain a carboxyl-containing silane coupling agent, and then performing graft modification on the nano silicon dioxide sol by using the carboxyl-containing silane coupling agent to obtain the modified nano silicon dioxide sol. The concrete disclosed by the invention is compact in internal structure, ultrahigh in compressive strength and breaking strength and high in durability and impact resistance, and the compressive strength during normal-temperature curing is stabilized to be 200MPa or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to an ultra-high performance concrete and a preparation method thereof. Background Art

[0002] Ultra-high performance concrete is a modern advanced cement-based material. It uses the principle of the closest packing between particles of different particle sizes, removes coarse aggregates, eliminates the influence of the coarse aggregate interface, and mixes a certain volume of high-strength fibers and highly active ultra-fine fillers to prepare ultra-high strength, high toughness, and high durability cement-based composite materials. Depending on its composition and curing treatment, ultra-high performance concrete has a compressive strength of 120-800MPa, a flexural strength of 20-50MPa, and a chloride ion permeability of less than 1 / 25 of that of high-strength concrete. It has extremely strong anti-penetration ability, an elastic modulus of 40GPa to 60GPa, and a fracture toughness of up to 40000J / m 2 , which is comparable to metal aluminum. The application of ultra-high performance concrete in engineering structures can solve the shortcomings of current high-strength and high-performance concrete, such as low tensile strength, high brittleness, and poor volume stability. At the same time, it can solve the problems of large investment, poor fire resistance, and easy corrosion of steel structures. It has very good application prospects in many fields such as military protection engineering, seaport engineering, underground engineering, bridge engineering, railway engineering, and structural earthquake resistance.

[0003] At present, research on ultra-high performance concrete has made certain progress. For example, patent CN101560082A discloses an ultra-high strength active powder concrete and its manufacturing method, in which AEA expansion agent, latex powder, polyester fiber and other components are added to the concrete, which respectively improve the pore structure of the active powder concrete, improve its density, improve adhesion, cohesion, reduce water absorption, reduce elastic modulus, enhance flexural strength, impact resistance, wear resistance, durability and crack resistance, and can improve and enhance the construction performance of active powder concrete. However, there are also some problems, such as the addition of latex powder, which will make the active powder concrete slurry more viscous and the operability particularly poor; it is easier to introduce bubbles during the mixing process, and due to the high viscosity, the bubbles inside are not easy to be discharged during the vibration process; in addition, the polymer has poor anti-aging and anti-ultraviolet capabilities, which limits its application scenarios; the latex powder is added in a large amount and the price is high, which increases the preparation cost of concrete.

[0004] For example, patent CN115872694A discloses a modified multi-walled carbon nanotube ultra-high performance concrete and a preparation method thereof. The present invention is based on the maximum packing density theory and uses powders of different particle sizes to form the most densely packed structure, ensuring that the ultra-high performance concrete has excellent mechanical properties such as compressive strength, flexural strength and fracture toughness. By adding ultra-fine mineral admixtures with an average particle size of 2 to 10 μm to the raw materials, it can be filled in the gaps between cement particles and quartz sand aggregates, which can effectively increase the compactness of the concrete, improve the pore structure in the concrete, and improve the concrete's impermeability and durability. However, carbon nanotubes have a very high specific surface area and aspect ratio, which increases the water demand of ultra-high performance concrete, increases viscosity, and makes construction operations difficult, affecting the engineering application of ultra-high performance concrete. At the same time, twisted steel fibers and carbon nanotubes are expensive, and require dispersion liquid for dispersion treatment, and the dispersion process is complicated, resulting in increased preparation costs.

[0005] The currently studied ultra-high performance concrete still has many defects, and its performance still needs to be improved. Therefore, the present invention provides a new ultra-high performance concrete and its preparation method and application. Summary of the invention

[0006] The purpose of the present invention is to provide an ultra-high performance concrete and a preparation method thereof in view of the deficiencies in the prior art. The concrete has a dense internal structure, ultra-high compressive and flexural strength, high durability and impact resistance, and the compressive strength under room temperature curing is stable at more than 200MPa.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] In one aspect, an ultra-high performance concrete comprises the following raw materials:

[0009] Cement, silica fume, mineral powder, fly ash, coarse sand, fine sand, high-performance water reducing agent, defoaming agent, retarder, water, steel fiber, modified nano silica sol, wetting agent; among them,

[0010] The modified nano silica sol is prepared by the following method: a double bond-containing silane coupling agent is reacted with olefinic acid to obtain a carboxyl-containing silane coupling agent, and then the nano silica sol is grafted and modified with the carboxyl-containing silane coupling agent to obtain the modified nano silica sol.

[0011] In a further embodiment, during the preparation of the modified nano-silica sol, the double-bond-containing silane coupling agent is selected from any one or more of γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltri(b-methoxyethoxy)silane and vinyltriethoxysilane.

[0012] In a further embodiment, during the preparation of the modified nano-silica sol, the olefinic acid is selected from any one or more of acrylic acid, hexene acid, and octenic acid.

[0013] In a further embodiment, during the preparation of the modified nano-silica sol, the nano-silica sol is prepared by any one of ion exchange, silicon powder hydrolysis, and silane hydrolysis; the average particle size of the nano-silica sol is 10 to 16 nm, the silica content is 29 to 31%, and the Na2O content is less than 0.5%.

[0014] In a further embodiment, the modified nano-silica sol is prepared by the following method:

[0015] (1) dissolving a double bond-containing silane coupling agent in anhydrous ethanol to obtain a silane coupling agent solution;

[0016] (2) adding an oxidant, an initiator and an olefinic acid to the silane coupling agent solution in sequence under stirring, aging for 1 to 2 hours, and then adding sodium hydroxide to adjust to neutrality to obtain a carboxyl-containing silane coupling agent;

[0017] (3) Adding propylene glycol to the nano-silica sol under stirring to react, then adding a carboxyl-containing silane coupling agent, keeping the temperature to react, and adding sodium hydroxide to adjust the pH value to 8-9 after the reaction is completed, thereby obtaining a modified nano-silica sol.

[0018] Preferably, in step (1), the mass ratio of the double bond-containing silane coupling agent to anhydrous ethanol is 1:(8-15); more preferably, the mass ratio of the double bond-containing silane coupling agent to anhydrous ethanol is 1:10.

[0019] Preferably, in step (2), the oxidant is selected from any one or more of hydrogen peroxide, peracetic acid, ammonium persulfate, and potassium persulfate; and the mass ratio of the oxidant to the double-bond silane coupling agent is (1-5):100.

[0020] Preferably, in step (2), the initiator is a mixture of a chain transfer agent and a reducing agent, the chain transfer agent is mercaptopropionic acid, thioglycolic acid, mercaptoethanol, mercaptopropanol, the reducing agent is one or more of sodium bisulfite, sodium hypophosphite, ferrous sulfate; the weight ratio of the chain transfer agent to the reducing agent is 1: (0.3-2.0). The mass ratio of the initiator to the double-bond silane coupling agent is (2-4):100.

[0021] Preferably, in step (2), the mass ratio of the olefinic acid to the double-bond-containing silane coupling agent is (10-30):100.

[0022] Preferably, in step (2), the order in which the oxidant, initiator and olefinic acid are added to the silane coupling agent solution is: the interval between the oxidant and the initiator is 5 to 10 minutes, the interval between the initiator and the olefinic acid is 5 to 10 minutes, the olefinic acid is added before the initiator, and the interval between the addition of the olefinic acid and the initiator is 10 to 20 minutes.

[0023] Preferably, in step (2), the reaction temperature is controlled at 50°C to 53°C.

[0024] Preferably, in step (3), the mass ratio of glycerol to nano-silica sol is (0.1-0.5):100.

[0025] Preferably, in step (3), the reaction temperature of the insulation reaction is 20 to 30° C., and the reaction time of the insulation reaction is 4 to 5 hours.

[0026] Preferably, in step (3), the mass ratio of the carboxyl-containing silane coupling agent to the nano-silica sol is (7.5-15):100.

[0027] In a further embodiment, the cement is P·O 52.5 cement.

[0028] In a further embodiment, the silicon content of the silica fume is ≥ 90%, and the specific surface area is ≥ 20000m 2 / kg.

[0029] In a further embodiment, the mineral powder is S95 grade mineral powder and / or S105 grade mineral powder.

[0030] In a further embodiment, the fly ash is primary ash.

[0031] In a further embodiment, the high performance water reducer is selected from polycarboxylate water reducer, and its water reduction rate is ≥30%.

[0032] In a further embodiment, the particle size of the coarse sand is 20 to 40 meshes.

[0033] In a further embodiment, the fine sand contains 40-120 mesh particles accounting for ≥90%.

[0034] In a further embodiment, the steel fiber has a diameter of 0.2 mm and a length of 12 to 25 mm.

[0035] In a further embodiment, the defoaming agent is selected from any one or more of dimethyl silicone oil, polysiloxanes, and polyethers.

[0036] In a further embodiment, the retarder is selected from any one or more of sucrose, sodium gluconate, glucose, sodium pyrophosphate, and citric acid.

[0037] In a further embodiment, the wetting agent is selected from at least one of sodium salt of dioctyl succinate anionic surfactant, α-olefin sulfonate, sodium benzyl sulfonate, and sodium salt of dialkyl succinate sulfonate.

[0038] The ultra-high performance concrete mentioned above comprises the following raw materials by weight:

[0039] 640-1000 parts of cement, 120-240 parts of silica fume, 150-300 parts of mineral powder, 80-200 parts of fly ash, 560-1500 parts of coarse sand, 240-700 parts of fine sand, 4-9 parts of high-performance water reducing agent, 0.4-1.0 parts of defoaming agent, 0.2-0.8 parts of retarder, 172-236 parts of water, 234-390 parts of steel fiber, 3-50 parts of modified nano-silica sol, and 1-10 parts of wetting agent.

[0040] Preferably, the ultra-high performance concrete comprises the following raw materials by weight:

[0041] 755 parts of cement, 140 parts of silica fume, 200 parts of mineral powder, 100 parts of fly ash, 650 parts of coarse sand, 400 parts of fine sand, 7 parts of high-performance water reducer, 0.5 parts of defoamer, 0.3 parts of retarder, 172-236 parts of water, 280 parts of steel fiber, 3 parts of modified nano-silica sol, and 3 parts of wetting agent.

[0042] On the other hand, the method for preparing the ultra-high performance concrete comprises the following steps:

[0043] S1. Prepare the components of ultra-high performance concrete according to the mix ratio;

[0044] S2, mixing cement, silica fume, fly ash and mineral powder and grinding them by ball milling to obtain a mixed powder;

[0045] S3, mixing the powder, coarse sand, fine sand, water reducing agent, retarder and defoamer, then adding water, modified nano silica sol and wetting agent, stirring evenly to obtain mixed slurry I;

[0046] S4, under stirring, adding the steel fiber to the mixed slurry and mixing well to obtain mixed slurry II;

[0047] S5. Pour the mixed slurry II into the mold, insert a comb-shaped scraper into the interior of the slurry, and scrape it along the vertical direction of the component force, repeat 3 to 6 times, vibrate for 10 to 30 seconds after scraping, seal, moisturize and maintain for 7 days, and then naturally cure to obtain ultra-high performance concrete.

[0048] In a further embodiment, in step S1, the ball milling time is 10 to 30 minutes.

[0049] In a further embodiment, in step S5, the comb-shaped scraper includes a straight rod, a support rod, and a tooth plate; the tooth plate is provided with a plurality of rake teeth extending downward, and the front ends of the rake teeth are bent to form a hook shape;

[0050] The tooth plate and the rake teeth are made of stainless steel, and the straight rod and the support rod are made of any one of wood, plastic and stainless steel;

[0051] The tooth spacing of the rake teeth is 10-30 mm, and the tooth length is customized according to the slurry thickness.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] 1. The ultra-high performance concrete of the present invention has a dense internal structure. Compared with the current ultra-high performance concrete which requires high temperature and high pressure steam curing, the concrete of the present invention can achieve ultra-high compressive strength and high durability by room temperature curing, and has good construction performance.

[0054] 2. The modified nano-silica sol is added to the concrete of the present invention. Compared with conventional nano-silica, the modified nano-silica sol is grafted with a silane coupling agent with a carboxyl group on the surface of the nano-particles, so that the nano-particles have the same negative charge and there is an electrostatic repulsion between the particles. At the same time, the organic alkyl group of the silane coupling agent provides a steric hindrance effect on the nano-silica particles, so that the nano-particles have better dispersibility and stability in the ultra-high performance concrete slurry, and the workability of the slurry is better, so that the role of nano-silica in blocking micropores is fully brought into play, and the packing density of the ultra-high performance concrete is further improved.

[0055] 3. The addition of a wetting agent to the concrete of the present invention reduces the surface tension of the ultra-high performance concrete slurry and improves the slurry's wrapping ability for the fiber; the wetting agent and the modified nano-silica sol cooperate and synergize with each other, so that the bonding force between the fiber and the interface is significantly increased, and the mechanical properties and durability of the ultra-high performance concrete are further enhanced.

[0056] 4. The present invention utilizes a simple comb-shaped structure to make the major diameter direction of most steel fibers in the concrete perpendicular to the force direction, thereby improving the mechanical strength while maintaining the same fiber content.

[0057] 5. The preparation method of the present invention is simple and has strong applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 1 is a schematic diagram of the structure of the comb-shaped scraper of the present invention; in the figure, 1 is a straight rod, 2 is a supporting rod, 3 is a tooth plate, and 4 is a rake tooth. DETAILED DESCRIPTION

[0059] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.

[0060] In the present invention, the nano silica sol is prepared by any one of the methods of ion exchange, silicon powder hydrolysis, and silane hydrolysis. In the following specific embodiments, the nano silica sol prepared by the ion exchange method is used as an example for illustration. The specific steps of preparing the nano silica sol by the ion exchange method are as follows:

[0061] (1) Using a cation exchange resin to perform ion exchange on diluted water glass (modulus of 3.60, silicate molar concentration of 1.5 mol / L) to remove sodium ions in the water glass, thereby obtaining a polysilicic acid solution. Using a NaOH solution as a stabilizer, the pH value of the solution is adjusted to 9 to obtain a polysilicic acid solution.

[0062] (2) The polysilicic acid solution after adding the stabilizer is subjected to a seed crystal preparation process. The pH value of the polysilicic acid solution is adjusted to 8 by dropwise addition of weak acid electrolyte oxalic acid, and the weak alkaline polysilicic acid solution is subjected to a hydrothermal reaction (hydrothermal reaction temperature 60° C., stirring rate 500 rpm) for 20 minutes to obtain a mother solution.

[0063] (3) Add the polysilicic acid solution obtained in step 1 to the mother liquor at a ratio of 1:20 by weight of mother liquor: polysilicic acid, control the solution temperature to 50°C, and add dropwise for 2 hours to ensure that the crystal nuclei in the mother liquor grow regularly, so as to obtain the desired silica sol product with appropriate colloidal particle size and uniform distribution.

[0064] (4) An ultrafiltration machine is used to dehydrate and concentrate the nano-silica sol product that has completed the crystallization process to increase the percentage of SiO2. The prepared nano-silica particle size is between 10 and 16 nm and the concentration is about 30%.

[0065] In the present invention, in order to make the major diameter direction of most of the steel fibers in the ultra-high performance concrete perpendicular to the force direction and improve the performance of the concrete, the present invention uses Figure 1 The comb-shaped scraper shown comprises a straight rod 1, a support rod 2, and a tooth plate 3; the tooth plate 3 is provided with a plurality of rake teeth 4 extending downward, and the front ends of the rake teeth 4 are bent to form a hook shape;

[0066] The tooth plate 3 and the rake teeth 4 are made of stainless steel, and the material of the straight rod 1 and the support rod 2 is selected from any one of wood, plastic and stainless steel;

[0067] The tooth spacing of the rake teeth 4 is 10-30 mm, and the tooth length is customized according to the slurry thickness, which can be 50 mm, 100 mm, 150 mm, or 200 mm.

[0068] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.

[0069] Embodiment 1~5:

[0070] An ultra-high performance concrete, the composition of which is specifically shown in Table 1 below:

[0071] Table 1

[0072]

[0073] The modified nano silica sol is prepared by the following method:

[0074] (1) Place 100 parts of G-570 silane coupling agent in a reaction container, add 1000 g of anhydrous ethanol, and stir until a solution is obtained to fully dissolve G-570;

[0075] (2) Adding 1 part of oxidant, 2 parts of initiator and 10 parts of acrylic acid to the silane coupling agent solution in sequence under stirring, the time interval between adding the oxidant and the initiator is 5 minutes, the time interval between adding the initiator and the acrylic acid is 5 minutes, the acrylic acid is added before the initiator, and the time interval between the addition of the acrylic acid and the initiator is 10-20 minutes;

[0076] (3) The solution was aged for 1 hour, sodium hydroxide was added, and the pH value was stabilized to 7.0 to obtain a neutral carboxylic acid-containing G-570 silane coupling agent;

[0077] (4) Take 200g of the prepared nano-silica sol in a three-necked flask, set the temperature to 25°C, add 0.4g of propylene glycol under stirring, and add carboxylic acid group-containing G-570 silane coupling agent dropwise after half an hour. The addition amount is 15g and the mixture is added within 1 hour. Keep warm and continue stirring for 4 hours, then adjust the pH to 8.5 with sodium hydroxide to obtain modified nano-silica sol.

[0078] Ultra-high performance concrete is prepared by the following method:

[0079] S1. Prepare the components of ultra-high performance concrete according to the mix ratio;

[0080] S2, mixing cement, silica fume, fly ash and mineral powder and ball-milling for 10 minutes to obtain a mixed powder;

[0081] S3, mixing the powder, coarse sand, fine sand, water reducing agent, retarder and defoamer, then adding water, modified nano silica sol and wetting agent diisooctyl sodium succinate anionic surfactant, stirring evenly to obtain mixed slurry I;

[0082] S4, under stirring, adding the steel fiber to the mixed slurry and mixing evenly to obtain mixed slurry II;

[0083] S5. Pour the mixed slurry II into the mold, insert a comb-shaped scraper into the interior of the slurry, and scrape it along the vertical direction of the force, repeat 6 times, vibrate for 30 seconds after scraping, seal, moisturize and maintain for 7 days, and then naturally cure to obtain ultra-high performance concrete.

[0084] Embodiments 6 to 8

[0085] The difference from Example 2 is that in the preparation process of the modified nano-silica sol, the selection and dosage of the olefinic acid and the diradical silane coupling agent are shown in Table 2 below.

[0086] Table 2

[0087] Group Enoic acid Containing double base silane coupling agent Example 6 acrylic acid Vinyltrimethoxysilane Example 7 Hexenoic acid γ-Methacryloyloxypropyltrimethoxysilane Example 8 Octenoic acid Vinyltriethoxysilane

[0088] Examples 9 to 12

[0089] The difference from Example 2 is that the wetting agent is different. The selection of the wetting agent is shown in Table 3 below:

[0090] Table 3

[0091]

[0092]

[0093] Example 13

[0094] The difference from Example 2 is that in the step (2) of preparing the modified nano-silica sol, the oxidant, the initiator and the acrylic acid are added at one time.

[0095] Comparative Example 1

[0096] The difference from Example 2 is that the modified nano-silica sol is prepared by modification of G-570 silane coupling agent only, and the total amount thereof remains unchanged. The specific preparation method is as follows:

[0097] (1) Place 100 parts of G-570 silane coupling agent in a reaction container, add 1000 g of anhydrous ethanol, and stir until a solution is obtained to fully dissolve G-570;

[0098] (2) Take 200g of nano-silica sol and add it to a three-necked flask, set the temperature to 25°C, add 0.4g of propylene glycol under stirring, and add G-570 silane coupling agent dropwise after half an hour. The addition amount is 15g and the mixture should be completed within 1 hour. Keep the mixture warm and continue stirring for 4 hours, then adjust the pH to 8.5 with sodium hydroxide to obtain the modified nano-silica sol.

[0099] Comparative Example 2

[0100] The difference from Example 2 is that the modified nano-silica sol is replaced by an equal amount of unmodified nano-silica sol.

[0101] Comparative Example 3

[0102] The difference from Example 2 is that no modified nano-silica sol is added.

[0103] Comparative Example 4

[0104] The difference from Example 2 is that no wetting agent was added.

[0105] Comparative Example 5

[0106] The difference from Example 2 is that no wetting agent and modified nano silica sol are added.

[0107] Test Example 1

[0108] The compressive strength and flexural strength of concrete were tested with reference to GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", and the durability of concrete was tested with reference to GB / T50082-2009 "Standard for Test Methods for Long-term Properties and Durability of Ordinary Concrete". The results are shown in Table 4 below.

[0109] Table 4

[0110]

[0111] The results show that the compressive strength of the concrete obtained by the present invention reaches more than 200Mpa, and the flexural strength and compressive strength are high. Compared with Example 2, the flexural strength and compressive strength of the concrete obtained by Comparative Examples 1-3 are significantly reduced, indicating that the addition of modified nano-silica sol helps to improve the mechanical properties of concrete. Compared with Example 2, the flexural strength and compressive strength of the concrete obtained by Comparative Example 4 are also greatly reduced, which shows that the addition of the wetting agent has a greater impact on the mechanical properties of concrete.

[0112] From the results of the electric flux after 56 days of standard curing, it can be seen that the electric flux of the concrete obtained by the present invention is below 10C, and the durability is excellent. Compared with Example 2, the electric flux of the concrete obtained by the comparative example is increased, which shows that the addition of modified nano silica sol and wetting agent in the concrete helps to improve its durability. From Examples 6-8, it can be seen that the selection of specific olefinic acid and silane coupling agent in the preparation process of modified nano silica sol helps to further reduce the electric flux of concrete and improve the durability of the final product concrete.

[0113] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. An ultra-high performance concrete, characterized in that: Contains the following ingredients: Cement, silica fume, mineral powder, fly ash, coarse sand, fine sand, high-performance water reducing agent, defoaming agent, retarder, water, steel fiber, modified nano silica sol, wetting agent; among them, The modified nano silica sol is prepared by the following method: a double bond-containing silane coupling agent is reacted with olefinic acid to obtain a carboxyl-containing silane coupling agent, and then the nano silica sol is grafted and modified with the carboxyl-containing silane coupling agent to obtain the modified nano silica sol.

2. The ultra-high performance concrete according to claim 1, characterized in that: The double bond-containing silane coupling agent is selected from any one or more of γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltri(b-methoxyethoxy)silane and vinyltriethoxysilane.

3. The ultra-high performance concrete according to claim 1, characterized in that: The olefinic acid is selected from any one or more of acrylic acid, hexene acid and octenene acid.

4. The ultra-high performance concrete according to claim 1, characterized in that: The modified nano-silica sol is specifically prepared by the following method: (1) dissolving a double bond-containing silane coupling agent in anhydrous ethanol to obtain a silane coupling agent solution; (2) adding an oxidant, an initiator and an olefinic acid to the silane coupling agent solution in sequence under stirring, aging for 1 to 2 hours, and then adding sodium hydroxide to adjust to neutrality to obtain a carboxyl-containing silane coupling agent; (3) Adding propylene glycol to the nano-silica sol under stirring to react, then adding a carboxyl-containing silane coupling agent, keeping the temperature to react, and adding sodium hydroxide to adjust the pH value to 8-9 after the reaction is completed, thereby obtaining a modified nano-silica sol.

5. The ultra-high performance concrete according to claim 1, characterized in that: The mass ratio of the olefinic acid to the double-bond silane coupling agent is (10-30):100; the mass ratio of the carboxyl-containing silane coupling agent to the nano-silica sol is (7.5-15):

100.

6. The ultra-high performance concrete according to claim 1, characterized in that: The wetting agent is selected from at least one of sodium salt of diisooctyl succinate anionic surfactant, α-olefin sulfonate, sodium benzyl sulfonate, and sodium salt of dialkyl succinate sulfonate.

7. The ultra-high performance concrete according to claim 1, characterized in that: The average particle size of the nano silicon dioxide sol is 10-16 nm, the silicon dioxide content is 29-31%, and the Na2O content is less than 0.5%.

8. The ultra-high performance concrete according to claim 1, characterized in that: The silicon content of the silica fume is ≥90%, and the specific surface area is ≥20000m 2 / kg.

9. The ultra-high performance concrete according to any one of claims 1 to 8, characterized in that: The invention comprises the following raw materials by weight: 640-1000 parts of cement, 120-240 parts of silica fume, 150-300 parts of mineral powder, 80-200 parts of fly ash, 560-1500 parts of coarse sand, 240-700 parts of fine sand, 4-9 parts of high-performance water reducing agent, 0.4-1.0 parts of defoaming agent, 0.2-0.8 parts of retarder, 172-236 parts of water, 234-390 parts of steel fiber, 3-50 parts of modified nano-silica sol and 1-10 parts of wetting agent.

10. The method for preparing ultra-high performance concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Prepare the components of ultra-high performance concrete according to the mix ratio; S2, mixing cement, silica fume, fly ash and mineral powder and grinding them by ball milling to obtain a mixed powder; S3, mixing the powder, coarse sand, fine sand, water reducing agent, retarder and defoamer, then adding water, modified nano silica sol and wetting agent, stirring evenly to obtain mixed slurry I; S4, under stirring, adding the steel fiber to the mixed slurry and mixing well to obtain mixed slurry II; S5. Pour the mixed slurry II into the mold, insert a comb-shaped scraper into the interior of the slurry, and scrape it along the vertical direction of the component force, repeat 3 to 6 times, vibrate for 10 to 30 seconds after scraping, seal, moisturize and maintain for 7 days, and then naturally cure to obtain ultra-high performance concrete.

Citation Information

Patent Citations

  • Ultrahigh-strength active powder concrete and preparation method thereof

    CN101560082A

Cited By

  • Anti-crack concrete and preparation method thereof

    CN120097690A

  • Preparation method of high-crack-resistance concrete waterproof compacting agent

    CN120349115A

  • A method for preparing a high crack-resistant concrete waterproofing and densifying agent

    CN120349115B